Monitoring experts - Yaron Azrieli (Theoretical Economics, 2021)
We study the design of contracts that incentivize experts to collect information and truthfully report it to a decision maker. We depart from most of the previous literature by assuming that the transfers cannot depend on the realized state or on the ex post payoff of the decision maker. The contract thus has to induce the experts to "monitor each other" by making the transfers contingent on the entire vector of reports. We characterize the least costly contract that implements any given vector of efforts and derive the cost function for the decision maker. We then study properties of optimal contracts by comparing the value of information and its cost.
Keywords: D82; D86; 330; Moral hazard; information acquisition; monitoring; value of information